PERHATIAN ORANG TUA PADA KEGIATAN BELAJAR PESERTA DIDIK DI KELAS XI IIS SMA NEGERI 1 SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Dewi Samarurok; Jon Adison; Wira Solina (Jurnal Inovasi Penelitian, 2021)
This research is motivated by the lack of parental attention to their children both in learning and in supporting facilities for children. This study aims to get a picture of parents' attention from the following aspects: 1) caring about their children's learning, 2) paying attention to their children's interests and needs in learning, 3) managing children's learning time, providing or completing children's learning tools. This type of research is descriptive quantitative. The study population was 136 students, the sampling technique was selected by proportional random sampling, namely 57 students. The research data were obtained through questionnaires and processed using percentage techniques. The results showed that parents' attention was seen from the following aspects: 1) caring about their child's learning was in quite a lot of criteria, 2) paying attention to the interests and needs in learning were in many criteria, 3) managing children's learning time, providing or completing children's learning tools are in quite a number of criteria.